Hydrological impacts of the conservation reserve program—a mini review - Spor Leal, Layda Belia; Roy, Tirthankar; Uden, Daniel R.; Schoengold, Karina (Frontiers in Water, 2024)
The Conservation Reserve Program (CRP) is a voluntary land conservation initiative implemented by the U.S. Department of Agriculture (USDA). The program aims to improve the natural environment and enhance wildlife by incentivizing landowners to convert sensitive agricultural land into vegetative cover. This mini review synthesizes known peer-reviewed research on the effects of CRP on hydrological processes, highlighting the effects on water quality, groundwater levels, surface water yields, surface water runoff, and effects on the hydrological cycle. These studies show that the CRP appears to have a positive impact on water quality, decreasing the levels of nitrogen and suspended solids. Furthermore, the CRP denotes positive results when used to manage excess runoff on surrounding land. Regarding groundwater volume, the impact of CRP varied by location and showed limited changes in volume. Despite these findings, this review highlights the need for further and continued research on the effects of CRP on hydrology to improve monitoring strategies and increase its benefits on the environment.